Awareness of Chronic Kidney Disease among Patients and Providers - Plantinga, Laura C. (2010)
Earlier recognition of chronic kidney disease (CKD) could slow progression, prevent complications, and reduce cardiovascular-related outcomes. However, current estimates of CKD awareness indicate that both patient- and provider-level awareness remain unacceptably low. Many of the factors that are possibly associated with CKD awareness, which could help guide implementation of awareness efforts, have yet to be fully examined. Also, little is known regarding whether increased patient or provider awareness improves clinical outcomes or whether there are possible negative consequences of awareness for CKD patients. Further research is necessary to continue to design and refine awareness campaigns aimed at both patients and providers, but there is an immediate need for dissemination of basic CKD information, given both the high prevalence of CKD and its risk factors and the low estimated awareness of CKD.